Beyond Growth-Centricity: A Sound Governance Framework for Sustainable Tourism through Multi-Stakeholder Co-Management and SDG-Based Evaluation - Fathimah Azzahro; Bayu Irwansyah; Galih Gumilar; Apri Kuntariningsih (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This study examines the integration of Sound Governance principles within the sustainable tourism policy cycle to address institutional fragmentation and evaluation inefficiencies in developing economies. Using a sequential explanatory mixed-methods design, the research develops a multidimensional evaluation framework aligned with the Sustainable Development Goals (SDGs), analyzing policy performance across five strategic domains: Economy, Social-Welfare, Culture-Education, Environment, and Governance. The quantitative phase utilizes 17 adapted SDG indicators to measure policy efficacy, while the qualitative phase employs semi-structured interviews and stakeholder mapping to deconstruct power dynamics in multi-actor co-management structures. The findings reveal that Sound Governance—specifically transparency and accountability—serves as a critical catalyst for policy effectiveness, significantly influencing destination sustainability through an input-process-output-outcome-impact pathway. Empirical evidence from the case of Penglipuran Village, Bali, corroborates these results, demonstrating that indigenous institutional legitimacy enhances social responsiveness but remains vulnerable to overtourism-driven economic dependency. Notably, the study demonstrates that integrating SDGs into the policy evaluation cycle transforms assessments from mere administrative formalities into strategic instruments for long-term demand stability and ecosystem preservation. These findings position Sound Governance as a strategic intangible asset, offering theoretical contributions to development administration and practical guidance for policy-makers navigating the complexities of sustainable destination management in competitive global markets